Tantangan dan Peluang dalam Meningkatkan Kompetensi Profesional Guru Pendidikan Agama Kristen di Era Society 5.0 - Endi Tanaem; Omega Bia; Nadap Rafi Ghungnga; Yosep Sudarso; Hemi Damnosel Bara Pa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Society 5.0 era brings profound transformation in education, requiring Christian Religious Education (PAK) teachers to integrate technology in learning while maintaining Christian values. This study aims to analyze the challenges faced by PAK teachers in improving professional competence in this era, as well as exploring existing opportunities. The method used is library research with a qualitative approach, collecting data from journals and related literature. The results of the study indicate that many PAK teachers are not ready to face change, so they need a systematic professional development program. In addition, digital technology offers innovative learning methods that can increase student engagement. This study recommends a holistic approach in developing teacher competence, by maintaining a balance between technology and spiritual values.